Molecular mechanisms of transport and metabolism of vitamin B12 in mycobacteria - Moosa, Atica (My University, 2013)
Mycobacterium tuberculosis (MTB) encodes three enzymes that are dependent on vitamin B12–derived cofactors for activity, including a B12-dependent methionine synthase (MetH). Previously, work in the Molecular Mycobacteriology Research Unit (MMRU) demonstrated vitamin B12 auxotrophy in a mutant strain disrupted in the alternative, B12-independent methionine synthase, MetE. This observation established the ability of MTB to transport corrinoids despite the absence of an identifiable B12-specific transporter. In addition, it suggested that MTB does not synthesize vitamin B12 in vitro. Notably, bioinformatic analyses identified PPE2 as the only B12-related transport candidate in MTB, though as a putative B12-regulated cobalt transporter. PPE2 is unusual in possessing directly upstream of its predicted start codon one of only two B12-dependent riboswitches in the MTB genome, and it lies in a putative operon with B12 biosynthetic genes, cobU and cobQ1. In this study, the possibility that PPE2 functions in the transport of vitamin B12 or cobalt was investigated. Transcriptional and phenotypic data suggested that PPE2 was not involved in B12 transport. Instead, it was shown that cobalt can supplement the growth of an MTB metE mutant in liquid medium, strongly supporting the ability of MTB to synthesize B12 de novo. Moreover, the ability to utilise exogenous cobalt was dependent on functional PPE2, thereby establishing a role for a PPE-family member in cobalt assimilation in MTB. Vitamin B12 comprises a central corrin ring co-ordinated to 5,6-dimethylbenzimidazole (DMB) as α-axial ligand. Substituting DMB with adenine yields the alternate form, pseudo-B12. The ability of mycobacteria to utilize pseudo-B12 precursors (cobinamide and adenine) to support full function of B12-dependent metabolic pathways was evaluated. Although the pseudo-B12 precursors appeared to complement chemically the mycobacterial B12 auxotrophs, growth of the mutants on cobinamide alone complicated this interpretation. To address this limitation, DMB synthesis was targeted by disrupting the MTB bluB homologue, Rv0306. Neither site-directed mutagenesis of key Rv0306 residues, nor full-gene deletion was sufficient to eliminate growth on cobinamide. Instead, this observation highlights the need to establish biochemically the nature of the active B12 form synthesized and utilized by MTB under different conditions. In combination, the results presented here support the inferred flexibility of vitamin B12 biosynthesis in MTB, and reinforce the potential role of B12-dependent metabolism in mycobacterial pathogenesis.
Keywords: Mycobacterium tuberculosis.; Mycobacterial diseases.; Vitamin B12.